2010
DOI: 10.1002/ejic.200900806
|View full text |Cite
|
Sign up to set email alerts
|

The Tricarbonyliron Chalcogenolates [(OC)3Fe(μ‐ESitBu3)]2 (E = S, Se, Te)

Abstract: The tricarbonyliron thiolate and selenolate [(OC)3Fe(μ‐ESitBu3)]2 (E = S, Se) were synthesized photochemically from the reaction of 2 equiv. of pentacarbonyliron with the dichalcogenides tBu3Si–E2–SitBu3 (E = S, Se). X‐ray‐quality crystals of the tricarbonyliron thiolate [(OC)3Fe(μ‐SSitBu3)]2 (monoclinic, P21/n) and selenolate [(OC)3Fe(μ‐SeSitBu3)]2 (monoclinic, P21/n) were grown from benzene. The cyclic voltammograms of [(OC)3Fe(μ‐ESitBu3)]2 (E = S, Se, Te) resemble each other. Electrochemical reduction at po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Oxidative addition of the disilyl disulfide to Fe(CO) 5 under UV irradiation gives the silylthiolate Fe 2 [ μ -SSi( t -Bu) 3 ] 2 (CO) 6 . 192 The volatile Fe 2 ( μ -SCF 3 ) 2 (CO) 6 was obtained by addition of (SCF 3 ) 2 to Fe 2 (CO) 9 . 193 The related reactions of Fe(CO) 5 with XSCF 3 (X= SMe, SCF 3 ) give trace amounts of “Fe 2 ( μ -S)( μ -SCF 3 ) 2 (CO) 6 ”, which, as mentioned elsewhere, could be a perthiolate Fe 2 ( μ -SCF 3 )( μ -S 2 CF 3 ) 2 (CO) 6 .…”
Section: Synthesis Of Diiron(i) Dithiolato Carbonyls From Iron(0) mentioning
confidence: 99%
“…Oxidative addition of the disilyl disulfide to Fe(CO) 5 under UV irradiation gives the silylthiolate Fe 2 [ μ -SSi( t -Bu) 3 ] 2 (CO) 6 . 192 The volatile Fe 2 ( μ -SCF 3 ) 2 (CO) 6 was obtained by addition of (SCF 3 ) 2 to Fe 2 (CO) 9 . 193 The related reactions of Fe(CO) 5 with XSCF 3 (X= SMe, SCF 3 ) give trace amounts of “Fe 2 ( μ -S)( μ -SCF 3 ) 2 (CO) 6 ”, which, as mentioned elsewhere, could be a perthiolate Fe 2 ( μ -SCF 3 )( μ -S 2 CF 3 ) 2 (CO) 6 .…”
Section: Synthesis Of Diiron(i) Dithiolato Carbonyls From Iron(0) mentioning
confidence: 99%
“…In a preceding study 5 we have already made a comparison of cyclopentadienyliron dicarbonyl complexes with two series of isoelectronic and largely isosteric ligands, namely PPh 2 Me, 6 [PPh 2 BH 3 ] − , 6 and [SiPh 2 Me] −7 and SPtBu 3 , 8 [SPtBu 2 BH 3 ] −8 and [SSitBu 3 ] − . 9 In this report we have concluded that, with respect to electron donor strength, phosphanyl borohydrides occupy an intermediate position between phosphanes (weakest donors) and silyl ligands (strongest donors). 5 The same is true for the thio derivatives, although the differences are smaller.…”
Section: Introductionmentioning
confidence: 84%
“…For background to this work, see: Kü ckmann et al (2005Kü ckmann et al ( , 2007Kü ckmann et al ( , 2008Kü ckmann et al ( , 2010; Lerner (2005); Sä nger et al (2012). For a previous (incomplete) structure determination of the title compound, see: Fadel et al (1979).…”
Section: Related Literaturementioning
confidence: 99%